IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL (SPM) PADA PELAYANAN KESEHATAN DIABETES MELLITUS (DM) DI PUSKESMAS BIROBULI - Andi Belgratia Bubun Bandaso; Hasbullah Hasbullah; Intam Kurnia; Mohammad Irfan Mufti (Kampus Akademik Publiser, 2024)
. This research aims to describe and explain the implementation of the SPM policy in Diabetes Mellitus (DM) health services at the Birobuli Community Health Center. This research method is a qualitative descriptive research method and data collection techniques are by means of observation, interviews and documentation. This research was conducted at the Birobuli Community Health Center using a purposive selection and selection technique for informants as many as 6 (six) people. This research uses aspects used by Donald Van Meter and Carl Van Horn, namely: 1. Policy Standards and Targets 2. Resources 3. Characteristics of Implementing Organizations 4. Communication between Implementing Organizations 5. Attitudes of Implementers 6. Social, Economic and Environmental Environments Political. Based on the results of research and discussion, standard variables and SPM policy targets for DM sufferers at the Bureaubuli Community Health Center still reached 80.13%, this figure has not yet reached the target set in Minister of Health Regulation No. 4 of 2019 because it is still hampered by the stages of data collection activities and early detection of DM sufferers. . Resource variables that do not fully support the implementation of the Diabetes Mellitus Health SPM at the Bureaubuli Community Health Center are also a factor in achieving the Health SPM target that has not reached 100%, such as human, financial and infrastructure resources that are still insufficient. The variable characteristics of implementing agents are related to the bureaucratic structure, norms and relationship patterns that are formed between policy implementers and have run well and in accordance with SOPs. Communication variables between implementers in implementing SPM policies for diabetes mellitus sufferers do not experience obstacles. The communication variable between implementers at the community health center is carried out directly because they are still in the same work area, while communication with implementers in the community is also carried out well and is supported by the use of online communication. The attitude/tendency variable of policy implementers such as the Health Service and the Bureaubuli Community Health Center gave a good response with the existence of a clear policy governing how to implement Diabetes Mellitus services in accordance with SPM Health standards. Economic, social and political environmental variables still have obstacles regarding all funding for SPM which must be accommodated with SPM. This means that in planning the Palu City regional budget, the SPM must be taken into account first in the budget planning. Apart from that, the economic capacity of the people of Palu City is also a supporting factor in the success of the Diabetes Mellitus Health SPM. Apart from that, political support is still lacking in perceived benefits in supporting DM health services that are in accordance with the SPM. The general conclusion is that the implementation of the Minimum Service Standards (SPM) policy in the Diabetes Mellitus (DM) Health Service at the Birobuli Health Center has not gone well.